2015
DOI: 10.1111/1365-2478.12264
|View full text |Cite
|
Sign up to set email alerts
|

The natural combination of full and image-based waveform inversion

Abstract: A B S T R A C TIntegrating migration velocity analysis and full waveform inversion can help reduce the high non-linearity of the classic full waveform inversion objective function. The combination of inverting for the long and short wavelength components of the velocity model using a dual objective function that is sensitive to both components is still very expensive and have produced mixed results. We develop an approach that includes both components integrated to complement each other. We specifically utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
46
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

6
3

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 19 publications
0
46
0
Order By: Relevance
“…Alternatively, Biondi & Almomin (2014) successfully inverts the full bandwidth of the data. Recently, the merger of migration velocity analysis with FWI (Symes 2008;Almomin & Biondi 2012;Allemand & Lambaré 2015;Wu & Alkhalifah 2015b;Alkhalifah & Wu 2016) has gained popularity in the context of improving the prospect of converging to a global minimum. Moreover, the isolation of desired wavenumbers in the gradient using conditioning and filtering (Albertin et al 2013;Tang et al 2013;Alkhalifah 2015;Kazei et al 2016) helps such convergence prospect.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, Biondi & Almomin (2014) successfully inverts the full bandwidth of the data. Recently, the merger of migration velocity analysis with FWI (Symes 2008;Almomin & Biondi 2012;Allemand & Lambaré 2015;Wu & Alkhalifah 2015b;Alkhalifah & Wu 2016) has gained popularity in the context of improving the prospect of converging to a global minimum. Moreover, the isolation of desired wavenumbers in the gradient using conditioning and filtering (Albertin et al 2013;Tang et al 2013;Alkhalifah 2015;Kazei et al 2016) helps such convergence prospect.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, RWI inverts mainly for the background model, like in MVA, without the need for extended images or angle gathers. Alkhalifah and Wu (2016); Wu and Alkhalifah (2015b) suggested a new objective function, which can use the information of both the diving and reflected waves to update the background in the case of isotropic media. They also proposed a scattering angle filter (Wu and Alkhalifah, 2015a) to clean up the gradient and admit only smooth update in the early iterations.…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic wavefield inversion of P-waves has been the focus of research and inversion implementations over the past few years (Tarantola, 1986;Xu et al, 2012;Alkhalifah and Wu, 2015). With the rise of full waveform inversion (FWI) and its possible use in delineating the reservoir, the elastic description of the Earth is drawing a lot of attention.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of a good initial guess of the background model, the optimization problem using gradient methods is not capable of providing low wavenumber updates. Thus, gradient based inversion methods tend to converge to local minima (Tarantola, 1986;Alkhalifah and Wu, 2015). Xu et al (2012), based on the work of Plessix et al (1995), suggested using the recorded reflections to predict the P-wave reflectivity using a migration/demigration process, referred to as RWI.…”
Section: Introductionmentioning
confidence: 99%